Islamic Memes as Media of Da'wah for Millennials Generations: Analysis of Visual Language On Islamic Memes With Illustration Style - Winny Gunarti Widya Wardani; Ahmad Faiz Muntazori (Cultural Syndrome, 2019)
Islam as a religion of da'wah has obliged every Muslim to play a role in spreading the truth of the Qur'an. In the era of information technology like today, the spread of Islamic teachings can be done in various ways, including through memes. For millennials who are proficient with technology, Islamic memes are an alternative media for da'wah. This is due to the power of memes in conveying messages through image visualization and humour-style text. Islamic memes are generally distributed via the internet and messaging applications on smartphones. Most Islamic memes are designed using illustration styles. To understand the visual language of memes, this study formulates the question: how to read visual signs in Islamic memes as da'wah media, because the types of da'wah in memes are not only in the form of written text but also in the form of images? This study uses a combination method, which combines quantitative and qualitative approaches. Quantitatively, this study collects data about the views of the millennial generation on the attractiveness of illustration-style Islamic memes. Whereas qualitatively, an analysis of samples of illustration-style Islamic memes uses semiotic theory to see the structure of design elements as the visual language of da’wah messages. The results of this study are expected to be a reference for the scientific field of visual communication design, as well as encourage the creation of more productive and communicative Islamic memes as da'wah media for millennial generations.